Association of Self-Reported Weight Change and Quality of Life, and Exercise and Weight Management Behaviors Among Adults with Type 2 Diabetes Mellitus: The SHIELD Study. (8th May 2012) - Grandy, Susan; Fox, Kathleen M.; Bazata, Debbra D.
Abstract : Purpose . This study examined the association between self-reported weight change and quality of life, and exercise and weight management behaviors among individuals with type 2 diabetes mellitus (T2DM). Methods . In the US SHIELD study, respondents reported whether they had lost or gained weight compared with 1 year earlier and completed the SHIELD-WQ-9 quality of life questionnaire as well as provided information on their exercise and weight management behaviors in the past 12 months. Results . Sixteen percent of the respondents reported gaining weight (n = 460 ), and 30% reported losing weight (n = 895 ). More respondents who reported losing weight exercised regularly, limited calorie and fat intake, and increased fiber, fruit, and vegetable intake compared with respondents who reported gaining weight (P < 0.01 ). For all nine aspects of daily life, a significantly greater proportion of respondents who reported losing weight reported improved well-being (12%–44%) compared with respondents who reported gaining weight (P < 0.0001 ). Conclusions . Self-reported weight loss was associated with improved well-being, better exercise, and weight management behaviors among individuals with T2DM.